Estradiol together with dydrogesterone in oral hormonal therapy of the menopausal period - Pertyński, Tomasz; Stachowiak, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2008)
Estradiol (E2) and dydrogesterone have been present in oral hormone therapy (HT) of the menopausal period for some years. E2/dydrogesterone preparations attainable in Poland at present show high therapeutic efficacy both as continuous (including low-dose) and sequential HT. This oestrogen-progestogen combination is characterized by an exceptionally advantageous pharmacological profile (with a favourable influence on lipid profile, carbohydrate metabolism, blood pressure or skin) and high therapeutic safety (an impact on endometrium, uterine bleeding profile and breast tissues). This type of HT should be one of the basic therapeutic options for menopausal women in need of hormonal treatment.